Information System For Administering Preclinical Clerkship In The Faculty Of Dentistry UMS - Dawud, Muhammad, Husni Thamrin, S.T., M.T., Ph.D (2015)
Preclinical Clerkship is a form of clinical skill training program to prepare an undergraduate dentistry student to conduct clinical clerkship. All students must take the training, which takes place in the Faculty of Dentistry of Universitas Muhammadiyah Surakarta. Every student must complete a number of requirements listed in the guidebook in order to pass the program. However, the number of students have grown and so is the number of patients that attend the clinic. This has extended the responsibilities the lab assitant poses. She has to generate report for all dentists, a report for every student, a report about most common diagnoses and several others. In order to increase the capacity of the laboratory assistant to generate the sheer number of the reports required, we have developed an information system that could make the generation of report more quickly. This project uses some methods such as directly interview with stakeholders, read the literature, get requirement analysis, make a UML Use Case & Class Diagram, and Business Process Model and Notation (BPMN) that help team to create the preclinical information system application program. The results of this project is desktop application that help laboratory assitant to record the data of instrument, consumable, treatment, paper discussion, and people involved in the activity and also generate the required report quickly